Semiotic Analysis of Comments on X: The Role of @um_fess in Shaping Public Opinion on the Non-Cash Payment Policy at UM - Rahmadina, Hanim; Shahrazade, Syalaisha Nabila; Todalani Kalumbang, Yuventia Prisca Diyanti (Jogjakarta Communication Conference (JCC), 2025)
The era of digitalization is an era where digital technologies such as computers and the internet play a major role in various aspects of human life. This era brings a lot of progress and convenience to human life, especially in the economic field. This can be seen from the payment system that began to shift from cash or cash to cashless or the use of e-wallets as payment transactions. This study aims to determine the role of social media X, especially on the @um_fess account, in forming public opinion on non-cash payment policies on the UM campus. In addition, this study wants to find out how social media can strengthen or change public opinion by connecting it with other signs in the social media environment. Researchers also want to know the interpretation of the formed public opinion. This research was conducted using the Content Analysis method with a qualitative approach and refers to the Diffusion of Innovation Theory and Semiotics Theory by Ferdinand De Saussure. The results of this study found that Twitter, especially the @um_fess account, has a role in shaping public opinion regarding non-cash policies on the UM campus. The public opinion formed mostly leads to negative comments and some there are also positive and neutral comments.